Detroit Paper - Some Aspects of the Commercial Manipulation of Aluminum (with Discussion) - C. F. Nagel (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
This paper is written primarily for those who are familiar with the processes mentioned but who desire a further insight into some of the fundamental principles. It does not give a complete description of the various practices employed in the working of aluminum and its alloys, but presents a few illustrations of the essential respects in which aluminum differs from other common metals, and emphasizes the controlling factors of the processes under consideration. Heat Treating Certain aluminum alloys are capable of having their mechanical properties greatly altered by a heat-treatment process. The degree of this irnprovement may be illustrated by some typical properties of dura-lurnin (Table 1). It is essential that the material be in the wrought condition in order to obtain rnaximum heat-treatment effects. In the case of duralumin, the process consists of heating the metal to a prescribed temperature and then quenching it. Immediately after quenching, the material is relatively soft though not as soft as in the annealed state. If allowed to stand at room temperature, the material changes, increasing in hardness and strength without loss of elongation, but at the expense of the plasticity. This action is very rapid at first, gradually diminishing in intensity and to all practical purposes being completed in about four days. This process of hardening is termed